Bahasa Arab dan Konsep I’jaz al-Qur’an (Kritik Pemikiran Louwis ‘Awad) - Kurniawan, Rahadian; Asmara, Musda; Hardivizon, Hardivizon (Institut Agama Islam Negeri Curup, 2021)
This article discusses the concept of I'jaz al-Qur'an and its relationship with Arabic as a form of criticism of the logos concept put forward by Louis Awad. This research is a literature review conducted by collecting related data sources to analyze the character's thought in question. The concept of I'jaz al-Qur'an is a study related to the faith of Muslims, in this case the existence of the al-Qur'an as Kalamullah. Among the Islamic scholars, two views have been very influential since this issue was raised, namely the Asy'ariyah and Mu'tazilah circles. These two groups agree to believe that the Qur'an is Kalamullah. However, in this case, Dr. Louwis expresses this opinion and relates it to the concept of Christian Logos, in which the concept of al-Qur'an, as the eternal Kalamullah (qadim) put forward by two major groups in Islamic Theology, is an adoption of the Christian Logos concept. The misappropriation of the information provided by Dr. Louwis shows his lack of understanding and mastery regarding the issues he addresses in his book. Not supported by historical facts and correct scientific studies, he conveyed in his book a form of hatred against Islam, the Koran and the Arabic language in particular and the Arab nation in general.